CORPORATE TAXATION AND BUSINESS LEGITIMACY IN INDONESIA - Yudha Pramana; Anis W. Hermawan (Scientia Integritas Utama, 2022)
Empirical gaps and juridical gaps related to business legitimacy can cause tax avoidance efforts carried out by certain corporate taxpayers. The observed gap can be seen from the compliance ratio of the submission of the Annual Notification Letter of Corporate Income Tax, which has not been satisfactory. In contrast, the juridical gap can be seen in the loopholes in the rules that are still used as a means to conduct corporate tax avoidance. So it needs normative juridical studies to produce the concept of business legitimacy in tackling corporate tax avoidance in Indonesia. This study concluded that consistent business legitimacy in the form of efficiency principles and tax principles that do not distort investment in tax laws and regulations would lead corporate tax-payers to avoid tax avoidance in Indonesia.